Ventilator Function Improvement in Patients Undergoing Regular Hemodialysis: Relation to Sex Diﬀerences - Peđa Kovačević; Amela Matavulj; Slavimir Veljković; Zvezdana Rajkovača; Nenad Ponorac; Jasminko Huskić (Biomolecules & Biomedicine, 2008)
Uremic lung is different entity then oedema present in cardiovascular diseases or in adult respiratory distress syndrome as well. This state is one of the possible complications in patients with chronic renal failure (CRF) receiving regular hemodialysis (HD). There are several studies suggesting that in these patients in 30-40% cases pulmonary hypertension was developed. It is known that patients with primary pulmonary hypertension have peripheral airway obstruction The data also showed that primary as well secondary pulmonary hypertension are more often developed in females; even real reason is still unknown. The aim of the study was to estimate the ventilator functionimprovement in patients with CRF receiving regular HD related to sex differences. The study population consisted in 39 patients with CRF, with no cardiac and pulmonary diseases. These patients were treated by regular hemodialysis using bicarbonate or acetate mode, respectively. They were divided into two groups according to the sex. Spirometry parameters before and after onset of hemodialysis were recorded. The results were analyzed using Student t-test and presented as mean +/-SD. All p values <0,05 were considered significant. The result showed that ventilatory function in male patients is significantly improved, especially VC and FEV1, whereas in female patientsimprovement had not statistical significance. It can be concluded that one of the possible reasons for slight improvement of ventilatorfunction in female patients is pulmonary hypertension.